Volume 4B: Combustion, Fuels and Emissions 2017
DOI: 10.1115/gt2017-64744
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Industrial Gas Turbine Combustor and Pollutant Formation Using LES

Abstract: An experimental variant of a commercial swirl burner for industrial gas turbine combustors operating at 3 bar is numerically investigated using high-fidelity Computational Fluid Dynamics models using STAR-CCM+ v11.06. This work presents the computational results of the SGT-100 Dry Low Emission gas turbine provided by Siemens Industrial Turbomachinery Ltd. The related experimental study was performed at the DLR Institute of Combustion Technology, Stuttgart, Germany. The objective of this work is to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Considering the simulation accuracy ability and cost, this simulation of the industrial gas turbine combustor is based on 3.5 million meshes. For the experiment comparison with simulation, this paper shows the temperature, CH 4 and CO 2 mass fraction measured by Stopper et al [34] and the outlet NO mass fraction given by Mallouppas et al [35] and Jaravel et al [36]. It should be noted that the experimental errors associated with the temperature measurement are estimated up to 13% for fully reacting products, and the experimental errors associated with species concentration are estimated 4% for CH 4 and 20% for CO 2 [9].…”
Section: Simulation Of An Industrial Gas Turbine Combustormentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the simulation accuracy ability and cost, this simulation of the industrial gas turbine combustor is based on 3.5 million meshes. For the experiment comparison with simulation, this paper shows the temperature, CH 4 and CO 2 mass fraction measured by Stopper et al [34] and the outlet NO mass fraction given by Mallouppas et al [35] and Jaravel et al [36]. It should be noted that the experimental errors associated with the temperature measurement are estimated up to 13% for fully reacting products, and the experimental errors associated with species concentration are estimated 4% for CH 4 and 20% for CO 2 [9].…”
Section: Simulation Of An Industrial Gas Turbine Combustormentioning
confidence: 99%
“…Therefore, controlling the maximum temperature is an effective way to control the NO emission. For the prediction of pollutant emissions from the combustor exit, this paper compared the NO emission with the measurement given by Mallouppas et al [35] and Jaravel et al [36]. It should be noted that the measurement of pollutants is carried out at 30 mm downstream, thus causing approximately 7.5% of air leakage [35], which is not considered in the simulation.…”
Section: Simulation Of An Industrial Gas Turbine Combustormentioning
confidence: 99%
See 1 more Smart Citation
“…being ∆ = C w V 1/3 a length scale parameter dependent of the cell volume V, and S w is a deformation parameter, dependent of the strain rate tensor. Here, the model constant was set to C w = 0.544, given that this value has been shown to provide acceptable results both for homogeneous isotropic decaying turbulence and for channel flows (see, for example, [23] or Malloupas et al [24]).…”
Section: Large Eddy Simulationmentioning
confidence: 99%
“…It should be noted that several other numerical works in the open literature have also simulated the SGT-100 combustor. However, these works have focused almost exclusively on the more acoustically stable operating condition at 3 bar (Case A) with the aim of evaluating the performance of different combustion, chemistry, radiation or adaptive mesh refinement models [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] . An isothermal flow case was furthermore simulated by Bulat et al, 65 who identified both a PVC and a central vortex core inside the combustion chamber, whereas Xia et al 66 studied the dispersion of artificially induced entropy perturbations.…”
Section: Introductionmentioning
confidence: 99%